Project Based Learning E-Module to Teach Straight-Motion Material for Prospective Physics Teachers - Suci Prihatiningtyas; Fatikhatun Nikmatus Sholihah (Jurnal Pendidikan Fisika, 2020)
This research is a research development using the ADDIE model. The product developed in this research is project based learning E-module. The stages that were passed in this study were Analysis, Design, Develop, Implement, and Evaluate. The research instrument was in the form of an E-module validity test sheet, an E-module readability sheet and an E-module user response questionnaire. Data analysis techniques using the feasibility test E-Module, E-Module Readability Test and the response of the use of E-Module. The conclusion of the study is that the E-module based on project based learning using the ADDIE model developed is suitable for use with revisions with an average percentage given by the validator of 84.5%. The results of the E-module readability test based on project based learning with an average percentage of 82.9%, which means the reader is at an independent or free level, which means the reader understands the contents of the E-Module reading that was developed. Overall students responded very well with an average percentage of 87.1% of the E-Module based on project based learning that was developed.